A Coluna Prestes em Santo Ângelo/RS: recorrendo-se ao passado para erigir um patrimônio - Vitor, Amilcar Guidolim (2012)
The Prestes Column was a rebel movement which from 1924 to 1927 protested against the governments of the presidents Artur Bernardes and Washington Luís and in Santo Ângelo/RS decisive moments occurred under the leadership of Luis Carlos Prestes, which made this Column run through Brazil during two years and three months. Based on this history, between 1994 and 1996 it was idealized and it was implemented in an initiative of the public power of Santo Ângelo city, a Memorial to the Column Prestes. The problem which delineates this work is about the social representation produced in Santo Ângelo against and in favor of the space which was built, establishing it, or not, as an expression of the santoangelense s cultural heritage. This work uses as methodology bibliographical and documental researches, the use of Oral History techniques, based on the direct contact with the people who created the Memorial, adding to that, the application of a questionnaire with students from the Basic Education checking their perceptions in relation to the Prestes Column Memorial, understanding it or not, as the expression of the cultural heritage of Santo Ângelo. The main objective of this investigation is to analyze and to evidence the social representation produced by social groups from Santo Ângelo in favor and against the creation of the Memorial, as well as trying to verify the motivations, the objectives and interests to create a place of memory in relation to the past of Prestes Column in Santo Ângelo, showing all the repercussion that this project had in the local community. Besides, it also has the objective of proposing a project to Santo Ângelo city of Patrimonial Education in the Prestes Column Memorial, which is going to allow students of the Basic Education from the city to know a little bit more about the history that it portrays and all the importance of its heap and preservation, allowing from this research on the reflection in relation to the conditions of infrastructure, heap and location of the Prestes Column Memorial, aiming its maintenance while a place of memory and expression of Santo Ângelo heritage. Therein, it is considered as main result of this work the elaboration of a primer which is going to give data to the teachers of the Basic Education from Santo Ângelo city, mainly from the municipal system, in order to the work in relation to the history of Prestes Column and the Prestes Column Memorial, having in view the students appropriation for the history as well as the space while expression of the cultural heritage of Santo Ângelo.